Efficiency, cytotoxicity, and survivability evaluation of Salmonella phage cocktail against Salmonella derived from broiler sources - Wattana Pelyuntha; Thamonwan Narkpao; David Yembilla Yamik; Pichamon Kiatwuthinon; Arsooth Sanguankiat; Attawit Kovitvadhi; Kitiya Vongkamjan (Veterinary World)
Background and Aim: Salmonella is a leading cause of foodborne illnesses worldwide, often linked to poultry products. Antibiotic resistance among Salmonella strains has increased the need for alternative decontamination strategies, such as bacteriophage (phage) therapy. This study evaluates the lytic efficiency, cytotoxicity, and survivability of a Salmonella phage cocktail derived from wastewater sources.